Desain Pengembangan E-Modul IPA Materi Kalor Berbasis Flipbook Maker Dalam Meningkatkan Motivasi Belajar Siswa Kelas V Di Sekolah Dasar - Irvin Novita Arifin; Rifda Mardian Arif; Vicka Mutiati Arifin; Yenti Juniarti; Icam Sutisna (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2023)
This study aims to produce a product development design for the Science E-Module Heat Material Based on Flipbook Maker to increase the learning motivation of fifth-grade students at 60 State Elementary Schools, East City, Gorontalo City. The method used in this study refers to the Hannafin & Peck model. Hannafin & Peck’s model is a product-oriented research model. This model means that the product produced in this research is prioritized. At the same time, the effect produced in this study is an e-module of heat material based on flipbook maker in improving learning motivation of fifth-grade students. The E-Module of heat material design based on Flipbook Maker, which is designed using the Flipbook Maker application, has very feasible criteria of 95%. Thus, the E-module (electronic module) of heat material science designed using the Flipbook Maker application is included in the possible standards, can be used in learning, and is believed to generate student motivation in education, train students to think high-level and master technology.